2021
DOI: 10.1002/ajim.23295
|View full text |Cite
|
Sign up to set email alerts
|

Health and safety risk perceptions and needs of app‐based drivers during COVID‐19

Abstract: Background: App-based drivers face work disruptions and infection risk during a pandemic due to the nature of their work, interactions with the public, and lack of workplace protections. Limited occupational health research has focused on their experiences.Methods: We surveyed 100 app-based drivers in Seattle, WA to assess risk perceptions, supports, and controls received from the company that employs them, sources of trust, stress, job satisfaction, COVID-19 infection status, and how the pandemic had changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…By engaging in in‐depth interviews with platform workers and managers, we were able to gain a grounded understanding of the COVID‐19‐related conditions of driver's work as well as their motivations and rationales for their actions related to COVID‐19 risk‐taking and protection. This study extends the limited literature on platform work and COVID‐19 risks faced by digital platform drivers 35 . We also provide recommendations on occupational health interventions for this sector.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…By engaging in in‐depth interviews with platform workers and managers, we were able to gain a grounded understanding of the COVID‐19‐related conditions of driver's work as well as their motivations and rationales for their actions related to COVID‐19 risk‐taking and protection. This study extends the limited literature on platform work and COVID‐19 risks faced by digital platform drivers 35 . We also provide recommendations on occupational health interventions for this sector.…”
Section: Discussionsupporting
confidence: 57%
“…It is surprising, given the technological sophistication of platform companies, that this innovation was not already in place. Finally, in a context where our study and others 19,35 have found that personal protective equipment was not always easily available, platform companies could provide more easily accessible personal protective equipment to workers, while also ensuring that it is of high quality.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…9 This can not only contribute to turnover 10 but also negatively impact well-being. 11 A recent survey of both EMTs and paramedics before the COVID-19 pandemic showed that 57% indicated a dependence on overtime, and 56% depended on working multiple jobs. 12 Dependence on extra work has been shown to increase the odds of job dissatisfaction and intent to leave EMS within 1 year.…”
mentioning
confidence: 99%
“…We recognize that their views could differ significantly from the frontline workers' perspective. For example, surveys among app-based drivers reported concerns of infection risks from interactions with the public and insufficient workplace protections such as access to personal protective equipment (PPE) ( 31 , 46 ). Delivery workers in the French gig economy also expressed concerns of financial precarity and lack of union support ( 1 ).…”
Section: Discussionmentioning
confidence: 99%